Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jog.14495
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA‐139‐5p from mesenchymal stem cells accelerates trophoblast cell invasion and migration by motivation of the ERK/MMP‐2 pathway via downregulation of protein tyrosine phosphatase

Abstract: Aim: Exosomes present essential roles for intercellular interaction via extracellular pathways during systemic dysfunctions, including preeclampsia (PE). Here, we assessed the specific mechanism of mesenchymal stem cells (MSC)-originated exosomes in PE. Methods: The effects of exosomes on trophoblasts were studied by EdU, wound healing, Transwell and TUNEL assays. By microarray analysis, we found that exosomes enhanced the microRNA-139-5p (miR-139-5p) in trophoblasts, and confirmed the target gene of miR-139-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Previous research has confirmed that exosomes play a role in multiple conditions, including PE [11,25,26]. Furthermore, trophoblast cell growth inhibition, and dysregulation of miRNAs are involved in the progression of PE [27,28]. In the current study, we found that the growth of trophoblast cells was significantly inhibited by miR-486-5p inhibitor carried by HPVEC-exo.…”
Section: Discussionsupporting
confidence: 70%
“…Previous research has confirmed that exosomes play a role in multiple conditions, including PE [11,25,26]. Furthermore, trophoblast cell growth inhibition, and dysregulation of miRNAs are involved in the progression of PE [27,28]. In the current study, we found that the growth of trophoblast cells was significantly inhibited by miR-486-5p inhibitor carried by HPVEC-exo.…”
Section: Discussionsupporting
confidence: 70%
“…Due in part to studying the paracrine effects of stem cell therapy, this speci c therapy has been mechanistically linked to the inherited functions of secreting exosomes [24]. Recently, research suggested HUCMSC-originated exosomes might be an innovative direction for therapeutic approaches against PE by accelerating trophoblast cell invasion and migration [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with HUCMSCs, the up-expressed proteins in HUCMSCexos were MMP2 (Matrix metalloproteinase 2, fold change = 14.7) and VCAN (versican, fold change = 11.7). Previous study showed that MSC-exo could promote the migration of endothelium cells by delivering MMP2 [21]. VCAN contributes to tissue development and maintenance by participating in cell adhesion, proliferation and angiogenesis via binding to ECM components [22].…”
Section: In Vitro Proangiogenic Effects Of Hucmsc-exosmentioning
confidence: 99%
“…From the four studies shown in Table 1 on testing MSC-derived EVs in models of preeclampsia, two were in vitro studies performed using HUVECs [ 159 ] or trophoblasts [ 160 ] as cell models, while the other two were in vivo studies performed in rat models of preeclampsia [ 161 , 162 ]. EVs derived from human decidua MSCs were found to enhance HUVEC proliferation by reducing inflammation and oxidative stress [ 159 ].…”
Section: Extracellular Vesicles From Mesenchymal Stem Cells For Thmentioning
confidence: 99%
“…The two studies that performed in vivo testing to investigate the effects of MSC-derived EVs in rat models of preeclampsia both used human umbilical cord MSCs as the cell source for producing EVs. One study using exosomes from the MSCs showed that these significantly lowered blood pressure and proteinuria in the animal model, both key features of preeclampsia [ 161 ]. From in vitro experiments performed in the same study, it was noted that the exosomes could promote trophoblast cell migration, invasion and proliferation while reducing apoptosis, possibly by transferring miR-139-5p to the trophoblasts and thereby regulating the ERK/MMP-2 pathway.…”
Section: Extracellular Vesicles From Mesenchymal Stem Cells For Thmentioning
confidence: 99%